(3MGTjI SfGfs - (3SfGf GdOjf jhSa GdQhejs
(3ChdgG (B:s
(3MeOG def dg elqf ef aVdg (B... (3bGd GdeUfa (B: (3GdefI dhGgH GdYbd bjd Ydjg GdefI ePeheI YbdG hYQaG hTQYG EP bO GTJgQ Hjf GdYbdGA ef Cgd GdYQa Gf GdefI JgOe GdUfjYI hbGd GddY JYGdi hdG JHWdhG UObGJce GdBjI (B...s
(3BNQgG (B:s
... (3hESfGO GdGNJQGY Edi GdeSGFd Hd Ydi GdfbO dOjf Yfg Cfg dG GYJOGO ddeSFdI HOhf GdOdjd hjOhf GdfcJI hef hLO OdjdG Ch fcJI ajgG (B.. (3Cf GdJhLjg GdChd ef gPjf GdJhLjgf EfeG JUdM EPG cGfJ GdOdGFd GdePchQI (B.. (3JeJ GdMGTjIs
(3JHUQI GdYfhGf (B:s
(3Ydi BOGH eMeO Hf CTQa GdSeQbfOjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf (B1\40s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdadSaI hGdefWbs